Cyclical development and community structure of the intertidal polychaete reefs in the Jeram Mudflat, Peninsular Malaysia / Eeo Jun Jie - Eeo , Jun Jie (2018)
It is interesting but not clear how “hard” polychaete reefs can grow up on soft-bottom mudflats in tropical waters. Such polychaete reefs are also generally unknown in terms of their community structure and duration of existence. Ecological aspects of the polychaete reefs on Jeram intertidal mudflat were studied to 1) elucidate the faunal succession during the life cycle of the reef, in terms of species composition and spatiotemporal abundance; 2) examine the accompanying changes of the adjacent mudflat community structure; and 3) determine the relationship between the reef cycle and the hydrometeorological factors such as the wind field, current, erosion and sedimentation. Samplings on the polychaete reefs and mudflat were carried out from June 2012 to January 2014 to study the physical environment and the macrobenthic community. The macrobenthos were examined on both spatial (horizontal and vertical distribution) and temporal (monthly changes) scales. The Jeram polychaete reef cycled through four phases within a year: pre-settlement phase (March–May), growth phase comprising primary (May –November) and secondary (October–January) successional stages, stagnation phase (December–January) and destruction phase (January–March). At the onset of the southwest monsoon (May), strong erosive forces initiate the reef’s primary succession of the growth phase where the dominant polychaete Sabellaria jeramae (>90 % of the reef macrobenthos density) colonise on the exposed lag deposits of shells. During the northeast monsoon (November–March), stronger depositional forces cover the developed reef with fine sediments. Subsequently, this reef is colonised by another polychaete, the spionid Polydora cavitensis during the reef’s secondary succession of the growth phase. Polychaetes are the only inhabitants living inside the ephemeral Jeram reef clumps during all successional phases of the reef cycle, with a total of 21 species. Overall, total polychaete abundance decreased from surface to deeper zones of the reef. S. jeramae dominated the entire reef depth during primary succession. A mixed S. jeramae–P. cavitensis community dominated the surface zone (depth= 0–5cm) during secondary succession, but no polychaetes except P. cavitensis were found at the surface zone during the stagnation phase. Five major taxa (Polychaeta, Anomura, Gastropoda, Caridea and Brachyura) dominated the immediate mudflat macrobenthos. However, the mudflat macrobenthos play no obvious or direct role in initiating the growth of the reef which is likely the result of settlement of dispersed polychaete larvae from unknown offshore reefs. Generally, the reef presence has a positive effect on the presence or abundance of surrounding mudflat macrobenthos such as mudflat polychaetes, shrimps, crabs and gastropods.